Use and management of tamarind (Tamarindus indica L., Fabaceae) local morphotypes by communities in Tigray, Northern Ethiopia. Issue 2 (2nd April 2020) - Girmay, Hailay; Tewolde-Berhan, Sarah; Hishe, Hadgu; Asfaw, Zemede; Ruelle, Morgan; Power, Alison
ABSTRACT: The population structure, phenotypic differences and ethnobotanical knowledge of tamarind ( Tamarindus indica L., Fabaceae) were studied in Kunama- and Tigrigna-speaking communities in the Tigray Regional State of Ethiopia. A vegetation survey on 902 plots of 400 m 2 each was conducted along riparian forests and farmlands. Seed and pod morphology of sweet and sour morphotypes was compared based on 6 pods/tree from 20 trees. Thirty-two key informants and 256 randomly selected general informants were interviewed about the use and management of tamarind. Tree densities differed significantly among sociocultural groups and land use. Relatively more trees (6.0–17.5 individuals per hectare) were found in riparian forests as compared to farmland (4.0–7.8). Stem diameter class distribution has a bell-shape, indicating a regeneration problem. Morphological characteristics (pod length, pod width, pod weight, seed weight, pulp weight, and the number of seeds per pod) differed significantly between sour and sweet tamarind morphotypes ( p < .05). Interviews identified seven use categories of tamarind, including human and veterinary medicines and five food types, with a greater number of uses mentioned within Kunama communities. Results can be used to support the sustainable use of tamarind in riparian forests and on farms, including conservation of varietal diversity based on the complementary knowledge of both communities.